Effective Project Management : Traditional, Agile, Extreme - Wysocki, Robert K. (John Wiley & Sons, Incorporated, 2019)
"Now in its seventh edition, this comprehensive guide to project management has long been considered the standard for both professionals and academics, with nearly 40,000 copies sold in the last three editions! Well-known expert Robert Wysocki has added four chapters of new content based on instructor feedback, enhancing the coverage of best-of-breed methods and tools for ensuring project management success. With enriched case studies, accompanying exercises and solutions on the companion website, and PowerPoint slides for all figures and tables, the book is ideal for instructors and students as well as active project managers. -- Provided by publisher.